2012
DOI: 10.3354/meps10019
|View full text |Cite
|
Sign up to set email alerts
|

Living on the edge: single-species dominance at the Pakistan oxygen minimum zone boundary

Abstract: Oxygen minimum zones (OMZs) are naturally occurring, low-oxygen water masses that create hypoxic conditions where they impinge on the seafloor. Their lower boundaries are characterised by elevated densities of hypoxia-tolerant fauna and an abundant food supply. The polychaete Linopherus sp. nov. (Amphinomidae) is the dominant taxon at the Pakistan margin (PM) lower OMZ, at near suboxic dissolved oxygen (DO) concentrations of 5 to 8 µM. We explored the response of Linopherus sp. nov. to gradients in oxygen and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 96 publications
3
10
0
Order By: Relevance
“…However, uptake by the polychaete Linopherus greatly exceeded that of the foraminifera when the sample from the shallower site was incubated with tracer under more oxygenated conditions, consistent with the previous experimental results of Woulds et al (2007). Jeffreys et al (2012) suggested that this polychaete may prey on foraminifera, as well as out-compete them for food, thereby keeping their densities low. Overall, these studies suggest that foraminifera are important in organic matter cycling at very low oxygen concentrations, but out-competed by metazoan macrofauna (notably polychaetes) where these are abundant outside the OMZ core.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, uptake by the polychaete Linopherus greatly exceeded that of the foraminifera when the sample from the shallower site was incubated with tracer under more oxygenated conditions, consistent with the previous experimental results of Woulds et al (2007). Jeffreys et al (2012) suggested that this polychaete may prey on foraminifera, as well as out-compete them for food, thereby keeping their densities low. Overall, these studies suggest that foraminifera are important in organic matter cycling at very low oxygen concentrations, but out-competed by metazoan macrofauna (notably polychaetes) where these are abundant outside the OMZ core.…”
Section: Introductionsupporting
confidence: 79%
“…The papers of Woulds et al (2007) and Jeffreys et al (2012) arose from a comprehensive study of carbon cycling by benthic communities during different seasons (spring inter-monsoon and late pre-monsoon, 2003) and at different water depths (140-1850 m) across the Pakistan margin OMZ (Cowie and Levin, 2009). Within the framework of this broader investigation, we focused on the calcareous foraminifera Uvigerina ex.…”
Section: Introductionmentioning
confidence: 99%
“…Benthic organisms have higher respiratory surface area, with respect to size or per unit mass, in waters with lower oxygen levels (Burd 1988, Lamont & Gage 2000, Jeffreys et al 2012). However, these adaptations to increase O 2 flux can increase the risk of exposure to sulfide.…”
Section: Sulfide and Hypoxia Tolerance In Neoproterozoic Oceansmentioning
confidence: 99%
“…Still, greater densities of individuals of G. diomedeae were observed at the 1,000-1,600 m depth range, much deeper than the OMZ core Papiol et al, 2017). In areas subjected to permanent oxygen depletion, large deposits of labile organic carbon enhance proliferation of deposit feeders and burrowers in narrow bathymetric ranges just below the OMZ cores, where DO is no longer a limiting factor (Jeffreys et al, 2012;Levin, Whitcraft, Mendoza, Gonzalez, & Cowie, 2009;Méndez, 2013;Smith et al, 2000). Among decapod crustaceans, Milne-edwards 1883) have similar diets, but the former species has lower feeding intensity and replaces the latter species in deeper water (Cartes, 1993a(Cartes, , 1993b(Cartes, , 1998.…”
Section: Discussionmentioning
confidence: 92%
“…Still, greater densities of individuals of G. diomedeae were observed at the 1,000-1,600 m depth range, much deeper than the OMZ core Papiol et al, 2017). In areas subjected to permanent oxygen depletion, large deposits of labile organic carbon enhance proliferation of deposit feeders and burrowers in narrow bathymetric ranges just below the OMZ cores, where DO is no longer a limiting factor (Jeffreys et al, 2012;Levin, Whitcraft, Mendoza, Gonzalez, & Cowie, 2009;Méndez, 2013;Smith et al, 2000). Among decapod crustaceans, benthic detritivores (the squat lobster Munidopsis depressa Faxon 1893) occur at high densities and dominate the community between 800 and 1,000 m in the Gulf of California, in an environment charac- the high correlation observed between DO and T, is consistent with the observation that ectothermic animals are restricted to speciesspecific temperature ranges (Ekau, Auel, Pörtner, & Gilbert, 2010;Frederich & Pörtner, 2000;Pörtner, 2001).…”
Section: Babamentioning
confidence: 92%